2021
DOI: 10.4269/ajtmh.20-1009
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Recommendations for Infection Prevention and Control Practices for Healthcare Facilities in Low- and Middle-Income Countries during the COVID-19 Pandemic

Abstract: Infection prevention and control (IPC) strategies are key in preventing nosocomial transmission of COVID-19. Several commonly used IPC practices are resource-intensive and may be challenging to implement in resource-constrained settings. An international group of healthcare professionals from or with experience in low- and middle-income countries (LMICs) searched the literature for relevant evidence. We report on a set of pragmatic recommendations for hospital-based IPC practices in resource-constrained settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…The lack of personal protective equipment (PPE), prolonged exposure to patients, and inadequate knowledge of the disease transmission among the healthcare providers may have increased such incidents (49,50). Increased awareness of self-protection, adequate supplies of PPE, and a prompt response may aid in decreased susceptibility of infection among healthcare workers (46,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of personal protective equipment (PPE), prolonged exposure to patients, and inadequate knowledge of the disease transmission among the healthcare providers may have increased such incidents (49,50). Increased awareness of self-protection, adequate supplies of PPE, and a prompt response may aid in decreased susceptibility of infection among healthcare workers (46,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Routes of infection can be patient-to-staff, patient-to-patient, and staff-to-staff [ 43 ]. The previous study in Japan reported that the staff-to-staff route accounted for 31% of NIs [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…HCWs tend to get infected, especially front-line nurses who are regularly in close contact with infected patients whilst administering physical care [ 43 , 46 , 47 ]. According to a previous survey in Japan, 52% of the staff infected were nurses [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations